Analisis Pengukuran Kinerja Supply Chain Management Pendistribusian Barang Pada PT Alfaria Trijaya Dengan Metode Supply Chain Operation Reference (SCOR) dan Analitycal Hierarchy Process (AHP) - Endang Suhendar; Arifia Nurfida; Mohammad Riski Borman; Khabib Nursahim (LPPM, 2025)
Competition in the industrial world is a major challenge for companies in carrying out the production activities. PT Alfaria Trijaya is a company that produces frozen chicken processing. The SCM (Supply Chain Management) concept has been implemented to regulate the flow of products from suppliers to the hands of end consumers. However, the company's supply chain experienced problems due to poor delivery processes such as production planning inconsistencies, demand fluctuations and late deliveries. The company felt the need to measure the performance of the company's supply chain. The objective to be achieved in this study is to find out how effective the supply chain implementation is at PT Alfaria Trijaya. The method used is the Supply Chain Operation Reference (SCOR) which is divided into five processes, namely Plan, Source, Make, Deliver and Return, and the Analytical Hierarchy Process (AHP) method. The final score is 89.72. Thus, the performance calculation in the case study into the good attribute performance position has a major influence, namely on the Make and Return processes and each return with a final value of 20.90 and 22.83 for the attribute needs to be maintained. However, there are three attributes with low final values, namely the Plan, Source, and Deliver processes, it is necessary to propose a strategy to be able to increase their value.